Amelioration of aggregate cytotoxicity by catalytic conversion of protein oligomers into amyloid fibrils. Issue 36 (14th August 2020) - Yang, Jie; Dear, Alexander J.; Yao, Qiong-Qiong; Liu, Zhenyan; Dobson, Christopher M.; Knowles, Tuomas P. J.; Wu, Si; Perrett, Sarah
Abstract : Peptide vesicles catalyze conversion of toxic amyloid oligomers into benign fibrillar species. Abstract : The aggregation of peptides and proteins into amyloid fibrils is a molecular self-assembly phenomenon associated with both biological function and malfunction, notably in the context of neurodegenerative diseases. Oligomeric species formed early in the aggregation process are generally associated with cytotoxicity. Extrinsic molecules such as peptides have been found to influence amyloid formation kinetics and regulate this cellular process. Here, we use single-molecule FRET and bulk assays combined with global kinetic analysis to study quantitatively the effect of an 8-residue peptide (LQVNIGNR) on fibril formation by the yeast prion protein Ure2. This peptide, which is derived from a segment of the Ure2 prion domain, forms vesicular assemblies that accelerate fibril formation of Ure2 by promoting conformational conversion of oligomeric intermediates into fibrillar species in a catalytic manner. This reduces oligomer longevity and consequently ameliorates cytotoxicity. The LQVNIGNR peptide was found to accelerate fibril formation of unrelated proteins including Tau and α-Synuclein, suggesting a general ability to catalyse fibrillation. This study provides a general strategy for investigating the microscopic mechanism of extrinsic factors on amyloid aggregation. This approach can readily be applied to other amyloid systems and demonstrates that acceleration of oligomer conversion is a promising strategy to reduce amyloid toxicity.